2017
DOI: 10.1126/scitranslmed.aah5084
|View full text |Cite
|
Sign up to set email alerts
|

BET bromodomain inhibition suppresses innate inflammatory and profibrotic transcriptional networks in heart failure

Abstract: Despite current standard of care, the average 5-year mortality after an initial diagnosis of heart failure (HF) is about 40%, reflecting an urgent need for new therapeutic approaches. Previous studies demonstrated that the epigenetic reader protein bromodomain-containing protein 4 (BRD4), an emerging therapeutic target in cancer, functions as a critical coactivator of pathologic gene transactivation during cardiomyocyte hypertrophy. However, the therapeutic relevance of these findings to human disease remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
211
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(236 citation statements)
references
References 71 publications
15
211
1
Order By: Relevance
“…Also, it acts as an important regulator in multiple cellular processes, and its inhibitor (JQ1) draws much attention for therapeutic effects against tumor growth (17). Emerging studies have shown a close association between chronic inflammation and diabetes (18), whereas it has been recently discovered that BRD4 regulates inflammation (19,20). Thus, we assume that BRD4 may be involved in diabetic IVDD, especially MMP-13 expression in NPCs.…”
mentioning
confidence: 93%
“…Also, it acts as an important regulator in multiple cellular processes, and its inhibitor (JQ1) draws much attention for therapeutic effects against tumor growth (17). Emerging studies have shown a close association between chronic inflammation and diabetes (18), whereas it has been recently discovered that BRD4 regulates inflammation (19,20). Thus, we assume that BRD4 may be involved in diabetic IVDD, especially MMP-13 expression in NPCs.…”
mentioning
confidence: 93%
“…Some of these studies showed that the inhibitors disrupt BRD4bound SEs, resulting in oncogene downregulation (Lovén et al, 2013;Pelish et al, 2015;Bhagwat Anand et al, 2016). These drugs also inhibit inflammation and ameliorate related diseases, including LPSinduced sepsis, EAE-based neuroinflammation, diabetes, and cardiovascular diseases (Nicodeme et al, 2010;Bandukwala et al, 2012;Anand et al, 2013;Belkina et al, 2013;Mele et al, 2013;Brown Jonathan et al, 2014;Fu et al, 2014;Duan et al, 2017). These drugs also inhibit inflammation and ameliorate related diseases, including LPSinduced sepsis, EAE-based neuroinflammation, diabetes, and cardiovascular diseases (Nicodeme et al, 2010;Bandukwala et al, 2012;Anand et al, 2013;Belkina et al, 2013;Mele et al, 2013;Brown Jonathan et al, 2014;Fu et al, 2014;Duan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These findings offered a possible mechanism of inhibitor action. These drugs also inhibit inflammation and ameliorate related diseases, including LPSinduced sepsis, EAE-based neuroinflammation, diabetes, and cardiovascular diseases (Nicodeme et al, 2010;Bandukwala et al, 2012;Anand et al, 2013;Belkina et al, 2013;Mele et al, 2013;Brown Jonathan et al, 2014;Fu et al, 2014;Duan et al, 2017). With these encouraging effects, BET inhibitors offer new therapeutic possibilities, mainly for blood cancers and inflammation (Belkina & Denis, 2012;Ceribelli et al, 2014;Berthon et al, 2016;Ghosh et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to assess whether TRIAGE could identify transcriptional signatures of therapeutic interventions in heart failure (HF). Previous studies have shown that the epigenetic reader protein BRD4, a member of the BET (Bromodomain and Extra Terminal) family of acetyl-lysine reader proteins, functions as a critical chromatin co-activator during HF pathogenesis that can be pharmacologically targeted in vivo (Anand et al, 2013;Duan et al, 2017;Spiltoir et al, 2013) to prevent and treat HF by targeting gene programs linked to cardiac hypertrophy and fibrosis (Duan et al, 2017). We analyzed RNA-seq data from adult mouse hearts where pre-established HF (transverse aortic constriction, TAC) was treated with JQ1.…”
Section: Determining the Regulatory Control Points Of Diseasementioning
confidence: 99%